British Royal and Japanese Imperial Relations, 1868-2018 : 150 Years of Association, Engagement and Celebration - Kornicki, Peter F. (Peter Francis); Cortazzi, Hugh; Best, Antony, 1964- (Book collections on Project MUSE., 2019)
This new study examines the history of the relations between the British and Japanese monarchies over the past 150 years. Complemented by a significant plate section, with many rarely seen historical photographs and illustrations, together with supporting chronologies, this volume will become a benchmark reference on the subject.